Evolutionary conserved lineage of Angela-family retrotransposons as a genome-wide microsatellite repeat dispersal agent - Smýkal, P; Kalendar, R; Ford, R; Macas, J; Griga, M (Heredity, 2009)
A detailed examination of 45 pea (Pisum sativum L.) simple sequence repeat (SSR) loci revealed that 21 of them included homologous sequences corresponding to the long terminal repeat (LTR) of a novel retrotransposon. Further investigation, including full-length sequencing, led to its classification as an RLC-Angela-family-FJ434420 element. The LTR contained a variable region ranging from a simple TC repeat (TC)(11) to more complex repeats of TC/CA, (TC)(12-30), (CA)(18-22) and was up to 146 bp in length. These elements are the most abundant Ty1/copia retrotransposons identified in the pea genome and also occur in other legume species. It is interesting that analysis of 63 LTR-derived sequences originating from 30 legume species showed high phylogenetic conservation in their sequence, including the position of the variable SSR region. This extraordinary conservancy led us to the proposition of a new lineage, named MARTIANS, within the Angela family. Similar LTR structures and partial sequence similarities were detected in more distant members of this Angela family, the barley BARE-1 and rice RIRE-1 elements. Comparison of the LTR sequences from pea and Medicago truncatula elements indicated that microsatellites arise through the expansion of a pre-existing repeat motif. Thus, the presence of an SSR region within the LTR seems to be a typical feature of this MARTIANS lineage, and the evidence gathered from a wide range of species suggests that these elements may facilitate amplification and genome-wide dispersal of associated SSR sequences. The implications of this finding regarding the evolution of SSRs within the genome, as well as their utilization as molecular markers, are discussed.
Keywords: Retroelements; DNA rostlinná; hrách setý; Pisum sativum; Microsatellite Repeats; molekulární sekvence - údaje; DNA, Plant; Molecular Sequence Data; Terminal Repeat Sequences; Genome, Plant; genom rostlinný; koncové repetice; retroelementy; mikrosatelitní repetice; Fabaceae